Technical drawing for engineering communication - Goetsch, David L.; Rickman, Raymond L. (Cengage Learning, 2016)
Offers a modern approach to technical drawing that combines the industry standards with technologies and software, resulting in a valuable, highly relevant resource you won't want to be without.